分泌型ホスホリパーゼA2によるアポトーシスに対するロイコトリエン受容体遮断薬の神経保護効果 - 矢上, 達郎; 山本, 泰弘; 高馬, 宏美 (日本薬理学会年会要旨集, 2022)
Neurological diseases e.g. brain ischemia are associated with mammalian secretory phospholipase A2 (sPLA2). The group IB sPLA2 (sPLA2-IB) induced neuronal cell death via apoptosis, which were accompanied with chromatin condensation and DNA fragmentation. Previously, we had established the sPLA2-IB-induced neuronal apoptosis as the in vitro model for cerebral ischemia. Prior to neuronal apoptosis, sPLA2-IB generates leukotrienes (LTs) via 5-lipoxygenase (LOX), which are increased in the ischemic brain. Recently, we reported that LOX inhibitors prevented neurons from the toxicity of sPLA2-IB, suggesting an involvement of LTs to the neurotoxicity of sPLA2-IB. In the present study, we evaluated protective effects of receptor antagonists for LTB4 (LY293111) and cysteinyl LTs (ONO-1078) in the primary culture of rat cortical neurons. The two LT receptor antagonists suppressed the neurotoxicity of sPLA2-IB in a concentration-dependent manner. sPLA2-IB shrank neuronal cell bodies and shortened neurites Both LY293111 and ONO-1078 ameliorated morphological degenerations such as shrank neuronal cell bodies and shortened neurites in the sPLA2-IB-treated neurons. Furthermore, these LT receptor blockers prevented neurons from the sPLA2-IB-condensed chromatin and fragmented DNA, suggesting an involvement of LTs in the sPLA2-IB-induced neuronal apoptosis.